EXORCISM IN THE BIBLE AND AFRICAN TRADITIONAL MEDICINE - Ahirika, Edwin (Journal of Dharma, 2006)
The belief in the omnipresence of various species of evil spirits, like jennies, ghosts, vampires, malignant disembodied ghosts, and vast hordes of hostile spirits which lurk in graves and solitary places, on mountains, in dens of the earth and in marshes, is a universal phenomenon which started in biblical times. They were believed and still are believed in modem time to be roaming about the streets, striding through the doors and walls of houses and are even born on the wings of mighty winds that sweep through lands and seas. Wherever they go they bring misfortune, sickness, and death in their train. The Babylonians thought demons to be malodorous. One of the evil spirits, Pazuzu designated as ‘son of Hampa’ was believed to be the King of evil spirits of the air responsible for spreading fever.1 Abney highlights Hebrews’ common belief that demons were ubiquitous and caused ill health and sickness such as fever, wasting conditions, leprosy, blindness, asthma, and headache.2 In African traditional society, a man’s mental instability and any sign of abnormal behaviour are not necessarily seen as a result of only physical distortion of the physiological process but something far more than that, like attack of wizards, witches, a god, an offended ancestor, an evil spirit, or demon. Biblio-Tradio task of healers, physicians, and exorcists is to keep off or drive out the malignant spirit and set the patient physically, mentally, and spiritually fit and free. Exorcism is, therefore, a biblical and traditional method and an aspect of healing. In this article we briefly discuss biblical concept of demonology, Jesus as an exorcist, exorcism in African Traditional healing and conclude with highlighting a common denominator of biblical exorcism and exorcism in African traditional medical service.